Franck-Condon Factors to High Vibrational Quantum Numbers V: O(2) Band Systems - Nicholls, R. W. (J Res Natl Bur Stand A Phys Chem, 1965)
Franck-Condon factors arrays have been computed numerically and are displayed to highest known vibrational quantum numbers for the following O(2) band systems: [Table: see text]